2021
DOI: 10.24843/eja.2021.v31.i10.p01
|View full text |Cite
|
Sign up to set email alerts
|

Diversitas Dewan Direksi dan Profitabilitas pada Perusahaan Terdaftar di Bursa Efek Indonesia

Abstract: The study discusses the problem of company performance by looking at the level of diversity of the board of education (gender, age, nationality and nationality), and the type of company. In this day and age, Diversity of workers and top management is one of the ways to increase productivity and work effectiveness of an organization. The study was conducted as a development of research that has applied hypothesis testing which is useful for testing how the influence of the independent variable on the dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
1
1
2
Order By: Relevance
“…This was supported by previous studies by Ramdhania et al, (2020) and Handayani & Panjaitan (2019) that gender diversity affects firm value. Unlike the study completed by Ullah et al (2019) and Dewi & Dewi (2016) found that board gender diversity has no influences on firm value.…”
Section: Figure 1 Average Company Value As Measured By Tobin's Q In T...contrasting
confidence: 72%
See 1 more Smart Citation
“…This was supported by previous studies by Ramdhania et al, (2020) and Handayani & Panjaitan (2019) that gender diversity affects firm value. Unlike the study completed by Ullah et al (2019) and Dewi & Dewi (2016) found that board gender diversity has no influences on firm value.…”
Section: Figure 1 Average Company Value As Measured By Tobin's Q In T...contrasting
confidence: 72%
“…With the diversity in the board of directors, the company's decision-making process will be increasingly dynamic to improve the performance of the company. The presence of women in the board of directors also helps increase investor confidence in the company, because the company will be considered to do good corporate governance so that investors are not hesitant to invest in Dewi (2016). This research had been supported by studies by Ramdhania et al, (2020) and dan Handayani & Panjaitan (2019) said that the board of directors' gender diversity has a beneficial impact on the worth of the company.…”
Section: Board Diversity Of Board Directors and Firm Valuementioning
confidence: 74%
“…Penelitian tersebut menemukan bahwa adanya wanita dalam komite audit dapat meningkatkan manajemen laba karena wanita dinilai lebih berhati-hati dalam melakukan audit perusahaan. Selain itu mengenai kinerja perusahaan seperti yang dilakukan oleh Yopie & Aw (2021) Sedangkan untuk wilayah terbanyak yang memiliki persentase direktur wanita tertinggi adalah Benua Eropa, Timur Tengah, dan Afrika dengan persentase (18%), kedua oleh Benua Amerika (12%), dan yang terakhir adalah Benua Asia (6%). Lima negara yang memiliki persentase wanita tertinggi merupakan negara maju yang memiliki kualitas pendidikan yang lebih baik dibandingkan negara berkembang seperti di Asia.…”
Section: Pendahuluanunclassified
“…Menurut penelitian Yopie & Aw (2021), tingkat edukasi tidak berpengaruh terhadap kinerja perusahaan. Latar belakang edukasi yang tinggi tidak tentu merupakan sebuah kewajiban dalam perwujudan dalam dunia usaha, namun wawasan tentang bisnis dan ekonomi merupakan nilai tambahan untuk mempengaruhi kinerja perusahaan dalam mengelola organisasi serta memberikan arahan yang baik pada perusahaan H6 : Tingkat edukasi CEO memiliki pengaruh negatif terhadap kinerja perusahaan.…”
Section: Pendahuluanunclassified